PENGARUH PERILAKU BERBELANJA ONLINE GENERASI-Z DENGAN KEMAJUAN TEKNOLOGI DIGITAL (Studi Kasus Mahasiswa Universitas Almuslim Bireuen) - M, Saleh; Wulan, Wulan (Ekonomika Journal, 2023)
Online shopping has become a popular culture that is developing at the moment. Developing along with the development of communication technology and the very rapid development of new internet-based media. This research aims to determine the online shopping behavior of Generation Z with the development of digital technology. The study was conducted on Almuslim University students. The research is quantitative and analyzed using regression analysis. The research took a sample of 71 students who actively shopped online. Based on the research results, it was found that digital technology has an influence on online shopping behavior in Generation - Z.